Supporting Learning in Primary Schools - Sage, Rosemary; Wilkie, Min. (Exeter : Learning Matters, 2003)
Reflecting current best practice this handbook informs teaching assistants on a range of issues including: communication skills, coping with the curriculum and what children at primary school need to learn, educational theory and the role of the assistant.
Includes bibliographical references (p. 99-104) and index.
Keywords: Teachers' assistants; Elementary school teaching; Education